Persepsi Kegunaan Aplikasi Smartphone Whatsapp Instant Messaging Pada Kalangan Pelajar - sasa ani arnomo (Universitas Putera Batam, 2015)
Smartphone applications has been growing rapidly with proven many applications that can be downloaded for free on the internet. One smartphone apps harnessed and used as this research is Whatsapp instant messaging. The application is a chat application that is popular amongst smartphone users. Whatsapp instant messaging applications facilitate communication between users free of charge for use of internet data connection to send messages, pictures, video, and voice communications. The object of the research is the students, where they use the application to obtain information and exchange of information among fellow students like the subject matter, schoolwork, extracurricular activities or activities. The purpose of the research conducted to determine how perceptions of the usefulness of whatsapp instant messaging applications on the students.